The Specificity of Electoral Volatility in European Parliamentary Elections - Turska-Kawa, Agnieszka (Political Preferences, 2014)
European Parliament elections are a special area for the analysis of electoral volatility understood as changes of electoral support for individual parties occurring in time. Firstly, it is so because they are referred to as second-order elections. Secondly, because despite their supranational character, voting behaviours occurring in them are to a considerable extent moderated by the national context. The article discusses the qualities of European elections which generate electoral volatility at various analysis levels.